2005
DOI: 10.1111/j.1525-1594.2005.29104.x
|View full text |Cite
|
Sign up to set email alerts
|

Image Processing Strategies Dedicated to Visual Cortical Stimulators: A Survey

Abstract: Multi-electrode devices are constantly evolving toward a state where complexity and reliability are adequate for providing a breakthrough in visual cortical stimulation allowing the blind to recover partial vision. Yet few research teams have focused on the development of the front-end subsystem that transforms an input image from a camera into stimulation commands. This article collects state-of-the-art knowledge about the appearance and organization of phosphenes, and previous work in image processing dedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…A description of surgical difficulties and expected phosphene maps has been published earlier (Srivastava et al 2007). A similar approach to generate phosphene has been suggested by Buffoni et al (2005).…”
Section: Introductionmentioning
confidence: 98%
“…A description of surgical difficulties and expected phosphene maps has been published earlier (Srivastava et al 2007). A similar approach to generate phosphene has been suggested by Buffoni et al (2005).…”
Section: Introductionmentioning
confidence: 98%
“…Image segmentation, edge detection [4] and stereo processing techniques for building disparity maps, have been used to aid in navigation. However, these methods do not permit actual object recognition, sought-after in this paper, which calls for more complex processing to adequately extract the information prior to stimulation.…”
Section: Related Workmentioning
confidence: 99%
“…Louis‐Xavier Buffoni et al (127) of the Ecole Polytechnique de Montreal (Montreal, Quebec, Canada) reported on the state‐of‐the‐art of multielectrode devices for providing a breakthrough in visual cortical stimulation allowing the blind to recover partial vision. Six image processing strategies that could be used in such a subsystem were presented from the most optimistic that use brightness modulation to emulate grayscale to the most conservative that use only on/off phosphene evocation.…”
Section: Visual Supportmentioning
confidence: 99%